THE PRESENCE AND DISPERSION PATTERNS OF FRUIT FLIES (Bactrocera sp.) (DIPTERA : TEPHRITIDAE) OF WAX APPLE (Syzygium samarangense) ORCHARD AT LANGKAT REGENCY, NORTH SUMATERA - Aprilia Putri, Kartika
Cultivation of wax apple (Syzygium samarangense) is one source of livelihoods in Langkat regency, North Sumatera. However, the obstacles encountered in harvesting period are fruit fly infestation which decreases the economic value. Minim understanding about fruit flies on wax apple orchard at Langkat regency. The aim of this research was to identify the species of fruit fly infested on wax apple S. samarangense and its parasitoid. The research conducted in December 2015 until February 2016 at wax apple orchard in Langkat regency, North Sumatera. Collection of samples of fruit flies taken from the trap by compounds 0.25 ml methyl eugenol as an attractant. Furthermore, fruit flies were collected into a vial containing 70% alcohol to be identified. Thirty kilos of invested wax apple was collected from the orchard (at Langkat regency : North Sumatera) by purposive sampling and bring to the laboratory, stored in a bucket for the periods of 7 to 10 days. All the pupae place individually in plastic tube until emergence. Adult flies and its parasitoid were collected and preserved in 70% alchohol for further identification. Identification was done using morphological characters such as the T shape of the abdomen, the wings, the shape of the thorax. Analysis of data using statistical methods ANOVA SPSS version 20 and determine the presence and dispersion patterns using Morisita dispesion index. The results of a sample collection of fruit fly traps that found 4 species of Bactrocera sp. (B. carambolae, B. papayae, B. dorsalis and B. umbrosa). That number of individuals for B. carambolae was 670, B. papayae was 56, B. dorsalis was 31 and B. umbrosa was 115. From 30 kilos of wax apple found 427 pupae which consist of 250 pupae emerge as fruit flies and 20 pupae emerge as parasitoid. Based on morphological character of fruit flies there were 4 species of Bactrocera sp. (B.albistrigata, B.dorsalis, B.papayae and B.carambolae). The number of individuals for B.albistrigata was 50, B. dorsalis was 56, B. papayae was 73 and B. carambolae was 71. Measurement of aedeagus and cell dm length was varied between species. Aedeagus and cell dm length of B.dorsalis were 2.79 ± 0.19 mm and 2.27 ± 0.28 mm, B. papayae were 3.1 ± 0.17 mm and 2.38 ± 0.3 mm, and B. carambolae were 2.33 ± 0.22 and 1.9 ± 0. 26 mm. The presence of fruit flies in fruit and traps can be seen from the results of the identification of the wax apple found 4 species of fruit flies (B. albistrigata, B. carambolae, B. papayae and B. dorsalis) and the traps found 4 species of fruit fly (B. umbrosa, B. carambolae, B. papayae and B dorsalis). Dispersion patterns of fruit flies in wax apple orchard can be seen from the arrest of a fruit fly trap. Each species of fruit flies were obtained showed clumped pattern of dispersion. In addition of fruit flies its also found the parasitoid of fruit on infested fruit. Parasitoids are natural enemies of fruit flies that attack the fruit fly eggs and larvae stage. The presence of 3 species of parasitoid of fruit flies that were Fopius vandenboschi was 5, Psyttalia sp. was 11, and Diachasmimorpha longicaudata was 4.